Difference between revisions of "2007 Cyprus MO/Lyceum/Problem 11"
I_like_pie (talk | contribs) |
(→Solution: You cannot use calculators in this competition (This was not a nescessary operation)) |
||
Line 5: | Line 5: | ||
==Solution== | ==Solution== | ||
− | <math>X=\frac{1}{2007 \sqrt{2006}+2006 \sqrt{2007}}=\frac{1}{2007 \sqrt{2006}+2006 \sqrt{2007}}\cdot\frac{2007 \sqrt{2006}-2006 \sqrt{2007}}{2007 \sqrt{2006}-2006 \sqrt{2007}}=\frac{2007\sqrt{2006}-2006\sqrt{2007}}{ | + | <math>X=\frac{1}{2007 \sqrt{2006}+2006 \sqrt{2007}}</math> |
− | + | <math>=\frac{1}{2007 \sqrt{2006}+2006 \sqrt{2007}}\cdot\frac{2007 \sqrt{2006}-2006 \sqrt{2007}}{2007 \sqrt{2006}-2006 \sqrt{2007}}</math> | |
− | <math>Y=\frac{1}{\sqrt{2006}}-\frac{1}{\sqrt{2007}}=\frac{\sqrt{2006}}{2006}-\frac{\sqrt{2007}}{2007}=\frac{2007\sqrt{2006}-2006\sqrt{2007}}{ | + | <math>=\frac{2007\sqrt{2006}-2006\sqrt{2007}}{2006 \times 2007}</math> |
+ | <math>Y=\frac{1}{\sqrt{2006}}-\frac{1}{\sqrt{2007}}=\frac{\sqrt{2006}}{2006}-\frac{\sqrt{2007}}{2007}=\frac{2007\sqrt{2006}-2006\sqrt{2007}}{2006 \times 2007}</math> | ||
<math>X=Y\Rightarrow\mathrm{ C}</math> | <math>X=Y\Rightarrow\mathrm{ C}</math> |
Revision as of 12:25, 6 May 2007
Problem
If and
, which of the following is correct?
Solution